A New Theory of Human Behavior and Motivation - Kopsov, Igor (Advances in Social Sciences Research Journal, 2021)
We introduce a novel and comprehensive theory of human behavior and motivation, which incorporates within it both the laws of biology and core aspects of the social sciences. In continuation of the governing postulates of natural sciences we formulate the principle of preservation as the primary law of psychology; provide precise criteria for the definition of basic human needs and uncover their origin; explore the relation between body and mind; and show correlations between individual and social perspectives of life. Subsequently, we integrate these concepts into a unified model of human behavior. We reevaluate the place of psychology within the overall domain of social science and postulate the key role of psychological drives in formation of social processes both in the current and historical perspectives. The paper signifies a step towards establishment of a common paradigm of psychology.